Development of Picture Story Book Learning Media as Literacy Material for Earthquake Disaster Mitigation Students of Tegal Ratu Cilegon State Elementary School Banten - Wukufahdini Trijayanti; Muzani Muzani; Cecep Kusnadi (Eduvest - Journal of Universal Studies, 2025)
This research on the development of picture storybook media aims to provide education as literacy material for elementary school students regarding earthquake disaster mitigation, especially in the Cilegon area, Banten, which is one of the earthquake-prone areas. This research aims to develop a picture storybook media entitled "I'm Not Afraid of the Earthquake!" and find out the feasibility of the picture storybook. The process of developing picture storybooks uses the Hannafin and Peck method with three processes, namely needs analysis, design, and development with each process going through an evaluation and revision process. Data collection was carried out using questionnaires. The type of data produced is in the form of quantitative data that is analyzed using assessment criteria guidelines to determine product quality. The validation results from experts stated that the product with an average percentage of 95% with a very decent category. The assessment of media experts obtained a score of 93% and the assessment of material experts obtained a score of 98% and the trial of student products obtained a score of 90% with the category. This development research can be concluded that picture storybook media is very feasible to use for elementary school students.